2011
DOI: 10.1186/cc10263
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan and mortality after coronary revascularisation: a meta-analysis of randomised controlled trials

Abstract: IntroductionPatients undergoing coronary revascularization often require inotropic support that has been associated with an increased risk for death and morbidity. The purpose of this study was to evaluate the effect of levosimendan versus control on survival after coronary revascularization.MethodsA systemic review and meta-analysis of the literature was carried out on published randomized controlled clinical trials that investigated the efficacy of levosimendan compared to other therapy in patients having co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 41 publications
3
43
0
4
Order By: Relevance
“…A number of small-sized prospective randomized trials have shown positive effects of prophylactic LS administration on postoperative cardiac performance [6, 7], renal function [8, 9], inflammation [10], demand on other inotropic drugs [11] as well as on short-term survival [12, 13]. However, the transferability of these excellent results to real-life practice has been questioned and, despite LS being one of the best-investigated drugs in cardiovascular medicine in the recent years, its prophylactic use in cardiac surgery has not become a widely established therapeutic concept.…”
Section: Introductionmentioning
confidence: 99%
“…A number of small-sized prospective randomized trials have shown positive effects of prophylactic LS administration on postoperative cardiac performance [6, 7], renal function [8, 9], inflammation [10], demand on other inotropic drugs [11] as well as on short-term survival [12, 13]. However, the transferability of these excellent results to real-life practice has been questioned and, despite LS being one of the best-investigated drugs in cardiovascular medicine in the recent years, its prophylactic use in cardiac surgery has not become a widely established therapeutic concept.…”
Section: Introductionmentioning
confidence: 99%
“…Responsiveness for levosimendan treatment may depend on additional, as yet unrecognized factors, nevertheless, similar to other types treatments [96], the reduction in BNP levels predicts a better prognosis [47]. These considerations notwithstanding, recent meta-analyses indicate that the use of levosimendan is associated with improved clinical outcomes (improved hemodynamic parameters and significant reduction in mortality) in critically ill patients requiring inotropic support [6,7], and improved survival in patients undergoing cardiac surgery [8,97,98]. In clinical practice, the exclusion or correction of hypovolemia is essential in all AHF patients pretreated with diuretics and/or vasoldiators before starting levosimendan infusion.…”
Section: Discussionmentioning
confidence: 98%
“…Результаты метанализа исследований, проведен ных с использованием левосимендана в кардиохирур гии, также демонстрируют хорошие показатели выжи ваемости в послеоперационном периоде [14]. Применение левосимендана сопровождается улучше нием показателей гемодинамики не только у пациентов с нормальной фракцией выброса левого желудочка [15], но и у пациентов с дисфункцией левого желудочка [10].…”
Section: таблица 2 характеристика показателей интра и послеоперационнunclassified